Progress of targeted FOX family therapy in ovarian cancer - Zhang, Hairong; Gong, Cuiping; Lv, Xin (Frontiers in Pharmacology, 2025)
Ovarian cancer (OC) remains one of the most lethal malignancies affecting women, largely due to its asymptomatic onset and the consequent challenges in early detection and diagnosis. This often results in delayed treatment and poor clinical outcomes. Among gynecological cancers, OC exhibits the highest mortality rate. While current therapeutic approaches such as surgery and chemotherapy provide initial clinical benefit, they are frequently undermined by high rates of recurrence and metastasis. Moreover, the pronounced heterogeneity of OC further complicates treatment, highlighting the urgent need for novel therapeutic targets and more effective strategies. The forkhead box (FOX) family of transcription factors comprises a large group of proteins involved in regulating gene expression across various biological processes. Dysregulation of FOX family members has been implicated in aberrant cellular behaviors, including uncontrolled proliferation, resistance to apoptosis, enhanced invasiveness, metastatic potential, and the development of drug resistance. Importantly, the functional roles of individual FOX proteins vary significantly depending on the tumor context, reflecting the functional diversity of this family. This review aims to provide a comprehensive overview of the emerging roles of FOX family members in the pathogenesis and progression of OC, as well as recent advances in FOX-targeted therapeutic strategies.